What are the most effective medical interventions for managing retinopathy of prematurity in preterm infants born ? : A Systematic Review - Roysam Azmal sitanggang; Sita Pradjnadewi (The International Journal of Medical Science and Health Research, 2025)
Introduction: Retinopathy of Prematurity (ROP) is a leading cause of preventable childhood blindness affecting preterm infants. Laser photocoagulation, the traditional standard of care, is effective but inherently destructive, leading to permanent peripheral visual field defects and a high incidence of myopia. The introduction of anti-Vascular Endothelial Growth Factor (VEGF) agents like bevacizumab offers a less destructive approach with the potential for better refractive outcomes. However, concerns regarding disease recurrence and potential systemic effects persist. This systematic review was conducted to evaluate and synthesize current evidence to determine the most effective medical interventions for ROP. Methods: This systematic review adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A comprehensive search was performed across PubMed, Semantic Scholar, Springer, and Google Scholar. Twenty-seven studies, including randomized controlled trials and comparative studies evaluating anti-VEGF therapies and laser photocoagulation, were included. The primary outcomes analyzed were disease regression, recurrence rates, and long-term structural and refractive outcomes. Results: The evidence consistently showed that both anti-VEGF therapy and laser photocoagulation are highly effective in achieving initial disease regression. A significant advantage for anti-VEGF therapy is more favorable long-term refractive outcomes, particularly a significantly lower incidence of high myopia compared to laser. However, this is counterbalanced by a variable but significant risk of disease recurrence following anti-VEGF monotherapy, a risk that is lower with laser treatment. Evidence also suggests clinical differences between agents, with one study finding a lower recurrence rate for bevacizumab compared to aflibercept. Conclusion: The optimal management for ROP requires balancing significant trade-offs. Anti-VEGF therapy is often the superior choice for posterior disease (Zone I) and offers the compelling benefit of better long-term vision by reducing high myopia. Conversely, laser photocoagulation provides a more definitive treatment with lower recurrence rates but at the known cost of peripheral vision. Combination strategies are emerging to leverage the strengths of both modalities. Ultimately, the treatment decision must be individualized, weighing the risk of recurrence and unknown systemic effects of anti-VEGF against the certainty of peripheral field loss and myopia from laser.